(3MGTjI Ydi RgQ GdQHjY aj ThGgO GdHOjYs
(3ChdgG (B:s
(3ef MeO Gdchf CSJeO GdJhajb hGdYhe , GdMeO ddg GdPi ChOY HQGYI GdHjGf ef TGA ef GdYHGO s
(3BNQgG (B:s
(3HGdhSjdI GdYXei hGdaVjdI GdcHQi ced LejY GdcJGH hGdMeO ddg Mb MeOg hUdi Gddg Ydi fHi GdQMeI hBdg s
(3HQSe NRGfI NdjaI GdSdWGf RjOGf GdaGWeis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs